A SWOT Analysis of the Food Security System in India - Dr. Reena Singh; Lalit Kumar (International Journal of Engineering and Management Research, 2020)
In this paper, we are showing that famines and mass hunger deaths were no longer a problem in independent India. This was owing to an increase in agricultural productivity as a result of the focus placed on agriculture, particularly cereal production, since the first Five Year Plan. We currently produce 105 million tonnes of rice and 94 million tonnes of wheat each year, which is sufficient to meet the needs of our enormous population while also successfully regulating the country's Public Distribution System. Food grains are distributed at subsidised rates to various strata of society under the PDS.